Egyptian criminals in suits- analytical study on the criminology of white collar crimes: special focus on Egyptian cases - Hassouna, Sue Ellen (AUC Knowledge Fountain, 2012)
Criminology is the science of crime and until the year 1939 crimes were limited to street or conventional crimes committed by criminals of lower socio-economic segments in the society. After 1939 the American criminologist, Edwin Sutherland, has challenged this stereotype of crimes and criminals through his introduction of white-collar crimes that are perpetrated by elite offenders. However, the term has been introduced and utilized for more than seventy years across criminologists and law enforcement agencies it is still a foreign concept to the Egyptian legal system; hence the Criminal Law Code is predominately focused on mainstream criminalities. This absence of adequate regard for white-collar crimes in Egypt has caused the increase of it. Therefore, this thesis aims to take the initiative to highlight the importance and need for the criminology of white-collar crimes and fill this serious knowledge gap and demonstrate benefits to the scholarship of crime in Egypt and in specific to the Egyptian Criminal Law that seeks to generally serve the protection of higher social goods. This academic goal will be achieved by means of adopting a criminological perspective approach in analyzing two Egyptian cases of white-collar crimes that are regulated by the same applicable law Competition Law; the Cement Cartel case and Ezz Rebars Steel case. These two cases are characteristic of Egyptian white-collar criminality and also represent two different and distinctive types of white-collar crimes, corporate and state-corporate crimes. This study is also supported by a theoretical framework using the rational choice theory of white-collar crimes which decidedly represents the most comprehensive theoretical approach to investigate the underlying reasons of why and how the given elite criminals violated the law. Finally, investigating these cases from a criminological perspective triggers the question of whether the Egyptian legal system is in need of a new criminal legislation for white-collar crimes.